Pengaruh Flash Sale dan Electronic Word of Mouth terhadap Keputusan Pembelian Produk Glad2Glow di Shopee pada Mahasiswi Prodi Manajemen Angkatan 2022 Universitas PGRI Adi Buana Surabaya - Nurcahyani, Devi; Annisa Ika Damayanti; Anisa Firdiani; Alladyis Febia Wahyuningtias; Agus Asmoro; I Made Bagus Dwiarta (Jurnal Manajemen Riset Inovasi, 2026)
The rapid development of digital technology has brought significant changes to electronic commerce activities in Indonesia. This advancement has encouraged the growth of the beauty industry, particularly skincare products, which increasingly utilize e-commerce platforms as a means of marketing and sales. Amid the intense competition on Shopee, Glad2Glow products have successfully attracted consumers' attention through various digital marketing strategies, such as flash sale programs and the dissemination of information through electronic word of mouth (e-WOM). This study aims to determine and analyze the influence of flash sales and electronic word of mouth on purchasing decisions for Glad2Glow products on Shopee among female students of the Management Study Program at PGRI Adi Buana University Surabaya. The research employed a quantitative method with a purposive sampling technique. Data were collected through questionnaires distributed to respondents who met the research criteria and were tested for validity and reliability before further analysis was conducted. The results indicate that flash sales and electronic word of mouth have a significant influence on purchasing decisions for Glad2Glow products. Promotional programs offering discounts within a limited time period are able to encourage consumers' purchase intentions. Meanwhile, information, reviews, and experiences shared by consumers through digital media also play an important role in shaping purchasing decisions. Simultaneously, both variables make a significant contribution to purchasing decisions for Glad2Glow products on Shopee.